Efeito do óleo essencial de Citrus aurantium dulcis sobre o craving em usuários de crack em estado de abstinência - Araújo, Poliana Rafaela dos Santos (2019)
With great potential for generating dependency, crack highlights Brazil as the emerging country with the largest consumer market in South America due to its low cost, easy administration and way of acting. In the search for treatment for drug withdrawal, the chemist is faced with difficulties related to withdrawal, a period in which intense desire for the substance, called craving, accompanies symptoms of anxiety and hinders the detoxification process. Thus, considering the results of essential oils (EO) of the Citrus species on anxiety, and the relationship between craving and anxiety in the individual in crack withdrawal, the present study had the objective of analyzing the efficacy of the use of EO of Citrus aurantium dulcis, by inhalation as a complementary therapy in the acute management of craving in users of crack in abstinence state. This is an experimental, double-blind randomized clinical pharmacological type test performed with inmates of two Therapeutic Communities and a Detoxification Unit in the state of Paraíba. The total sample of 35 volunteers was subdivided into six groups according to the service, and, in a random way, in groups that would receive the experimental substance, aromatic control and control. For the analysis of the profile and anxious state, the Trait-State Anxiety Inventory (IDATE) was used and for the measures of craving levels the Cocaine Craving Questionnaire-Brief (CCQB) instrument was used. The experiment was developed in single and individual sessions, divided into three moments (basal, inhalation and post-inhalation), with the measurement of the parameters before and after inhalation. The results show that the abstinent crack users in the services presented a profile of high anxiety consistent with the alteration of the emotional activities resulting from the action of the drug in the brain reward system. After inhalation of Citrus Aurantium dulcis EO, there was a significant decrease in physiological parameters, in order to approximate the measurements of the standard considered normal for an adult, and an acute reduction of anxiety and craving in a correlated way. Thus, according to the results obtained, it is suggested that, in the situation described by the study, aromatherapy seems to have been effective in controlling the conditions generated by crack withdrawal syndrome.